A STUDY OF HIGH TRANSVERSE-MOMENTUM ELECTRONS PRODUCED IN PPBAR COLLISIONS AT 540 GEV - Bagnaia, P; Banner, M; Battiston, R; Bloch, P; Bonaudi, F; Borer, K; Borghini, M; Burger, J; Cenci, P; Chollet, J; Clark, A; Conta, C; et al. (Springer-Verlag, 1984)
The production of electrons with very high transverse momentum has been studied in the UA2 experiment at the CERN Mathematical expression collider ( Mathematical expression=540 GeV). From a sample of events containing an electron candidate with pT>15 GeV/c, we extract a clear signal resulting from the production of the charged intermediate vector boson W±, which subsequently decays into an electron and a neutrino. We study the W production and decay properties. Further-more, we refine our results on the production and decay of the neutral vector boson Z0. Finally, we compare the experimental results to the predictions of the standard model of the unified electro-weak theory. © 1984 Springer-Verlag.